Nitrogen fertilization at tillering of black-oat in two soil fertility conditions - Nakagawa, João; Cavariani, Claudio; Machado, José Ricardo (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to study the effect of six doses of N (0, 20, 30, 40, 50 and 60 kg/ha) applied at the end of tillering stage, on yield and seed quality of Avena strigosa Schreber cv. Comum, under two conditions of soil fertility. The experiments were carried out under field conditions on a Ultisol (distrophic Terra Roxa Estruturada), in Botucatu, SP, Brazil. The soil with less fertility (fallow land) presented 35% of soil base saturation. The soil with high fertility (previously with potato crop) had 49% of soil base saturation and received lime to increase it to 70%. All plots received basal fertilization of 20, 80 and 40 kg/ha of N, P2O5 and K2O. The yield and seed germination were not affected by N top dressing under both soil conditions. Under high fertility soil, the 60 kg/ha of N dose gave rise to the lodging and the decrease of the hectolitric weight of the seeds. Under less fertility soil, the N fertilization increased the dry weight of aerial part and improved the seed protein content at the highest dose of N.
Keywords: Avena strigosa; seed; nitrogen; lodging; dry matter; aerial parts; weight